Cutting-Edge Dynamics of Drone Technologies: Military Strategies and Peaceful Innovations - Simpson, Erika (In Factis Pax: Journal of Peace Education and Social Justice, 2024)
This article examines recent evidence and expert opinions on the pros and cons of unmanned aerial vehicles (UAVs), commonly known as drones. It analyzes the nuanced advantages and disadvantages of utilizing drones for both peaceful and military purposes. Rather than advocating for a blanket ban on drones due to their potential use in targeting individuals, such as al-Qaeda operatives in Pakistan or Russian soldiers in the Ukraine-Russia conflict, the article adopts a comprehensive approach by engaging with contemporary literature that assesses the complex implications of drone technology. The analysis highlights the potential benefits of drones in peaceful applications, including enhanced surveillance capabilities and their role in humanitarian efforts like disaster response and environmental monitoring. It also addresses significant ethical, legal, and operational concerns related to military use, such as accountability, the risk of civilian casualties, and the implications for international military power dynamics. Based on this assessment, the article presents specific recommendations for the international community and regional groups, emphasizing the establishment of regulatory frameworks that promote responsible drone use, prioritize transparency and accountability, and ensure compliance with international humanitarian law, thereby fostering international dialogue and cooperation.